Phakomatoses and Their Tumors : Genetics and New Treatment Options - Malik, Muhammad Taimur (IntechOpen, 2017)
In addition to sporadic primary neoplasms of the central nervous system, several genetic syndromes associated with CNS tumors have been identified. Tuberous sclerosis, neurofibromatosis-1 and -2, and von Hippel–Lindau syndrome belong to a collection of disorders called phakomatoses, which include both CNS tumors and cutaneous manifestations. The underlying genetics of these disorders are being elucidated and offer novel therapies for intervention.